Norma subjektif dan sikap dalam mendorong minat beli generasi milenial terhadap organic food - Rizkiawan, Ilham Karin; Aisah, Nurul; Utomo, Fahman Hadi (Nur Science Institute, 2024)
This study aims to understand a person's perception of other people's beliefs and how it affects their decision to buy organic food. This study also evaluates the influence of subjective norms and attitudes on the interest in buying organic food among the millennial generation in Karangmalang Village, Sragen. The object of this study was in Karangmalang Village, Sragen. The method used was quantitative, with data analysis using Partial Least Square (PLS), and involved 152 respondents as research samples. The findings showed that subject norms had a significant positive effect both directly and indirectly on consumer purchasing interest and attitudes. Implications of this study Millennial awareness of health opens up opportunities for producers to increase production and availability of organic food. Producers must explain the differences and advantages of organic food in order to attract young consumers' buying interest.